Can we resolve the taxonomic bias in spider venom research?. (January 2019) - Herzig, Volker; King, Glenn F.; Undheim, Eivind A.B.
Abstract: The rate of discovery of new spider species greatly exceeds the rate of spider venom characterisation, leading to an increasing number of species with unstudied venoms. However, recent advances in proteomics and genomics that enable the study of venoms from smaller species has expanded the accessible taxonomic range. Thus, although the number of unstudied spider venoms is likely to further increase, future research should focus on the characterisation of venoms and toxins from previously unstudied spider families. Highlights: The rate of discovery of new spider species by far exceeds the rate of spider venom characterisation. Advances in proteomics and genomics techniques now allow the study of venoms from a much wider taxonomic range. Closing the taxonomic gap at the family level should be the main focus for toxinologists over the next decade.